THE INFLUENCE OF WATER HARDNESS ON GIANT FRESHWATER PRAWN (Macrobrachium rosenbergii de Man) SPAWNING AND EGG PRODUCTION - M. Fatuchri Sukadi (Research Center for Fisheries, 1995)
The influence of water hardness on spawning and egg production of giant freshwaterprawn, Macrobracbium rosenbergii de Man was investigated in indoor tanks during a132 day study.